How do the women control their language Facing Certain Condition? a Perspective of Psychopragmatics - Rahmat, Wahyudi; Lateh, Nor Hazwani Munirah; Kurniawan, Yohan (Universitas Negeri Makassar, 2022)
There has been a growing interest in gender and language in recent decades. This study examines how women control their language facing specific, especially when angry.Â Minangkabau women are a subject in this research. The gap that underlies this study is that a Minangkabau woman, popular with polite language as a medium for language, is required to manage her anger in a speech in everyday life with its politeness. Conversation analysis is emphasized to explore forming a speech act in gender interactions in wedding cooking sessions and grocery shopping. These data are the words of Minangkabau women when interacting in the cooking process for weddings in several places in West Sumatra, Indonesia. A total of 17 Minangkabau women participated in the conversation. The concept of forming a speech ac related to how Minangkabau women speak the psychopragmatic approach used in analyzing the data. The results revealed four forms of Minangkabau women's angry language when interacting in the cooking area for marriage and grocery shopping. The implication is related to participants' relationships, closeness, and social status. This suggests that those three values are ingrained in Indonesian culture.